Native T1 Mapping and Extracellular Volume Mapping for the Assessment of Diffuse Myocardial Fibrosis in Dilated Cardiomyopathy - Nakamori, Shiro; Dohi, Kaoru; Ishida, Masaki; Goto, Yoshitaka; Imanaka-Yoshida, Kyoko; Omori, Taku; Goto, Itaru; Kumagai, Naoto; Fujimoto, Naoki; Ichikawa, Yasutaka; Kitagawa, Kakuya; Yamada, Norikazu; et al. (JACC. Cardiovascular imaging, 2018)
The purpose of this study was to examine the histological correlation of native myocardial T1 and extracellular volume fraction (ECV) measurement at 3-T for the assessment of diffuse pathological changes in the myocardial tissue, including myocardial fibrosis and extracellular space in dilated cardiomyopathy (DCM). Cardiac magnetic resonance T1 techniques allow the quantification of diffuse myocardial fibrosis. However, there are no definitive head-to-head studies of native T1 versus ECV for the detection, quantification, and characterization of pathological changes in the myocardial tissue in DCM by using histological samples for confirmation. A total of 36 subjects with DCM (31 men, mean age 56 ± 16 years) underwent pre- and post-contrast T1 mapping as well as late gadolinium enhancement (LGE) cardiac magnetic resonance at 3-T. Biopsy samples were used for the quantification of collagen volume fraction using picrosirius red staining and an extracellular space component from hematoxylin and eosin–stained myocardium. Nonischemic LGE was observed in 14 of 36 patients. Although patients with LGE had significantly greater biopsy-proven collagen volume fraction than those without LGE (21 ± 12% vs. 11 ± 8%; p < 0.01), there was substantial overlap of collagen volume fraction values between patients with and without LGE. Both native T1 value and ECV were similarly and significantly associated with biopsy-proven collagen volume fraction (r = 0.77 and r = 0.66, respectively; p < 0.05). Furthermore, ECV had a strong correlation with the biopsy-proven extracellular space component (r = 0.86), whereas native T1 had only a moderate correlation (r = 0.55). Interobserver and intraobserver reproducibility for native T1 and ECV were 0.89, 0.95, 0.96, and 0.98, respectively. Native T1 exhibited comparable ability as ECV measurement in the detection and quantification of histological collagen volume fraction, with high reproducibility, and therefore diffuse myocardial fibrosis in DCM may be reliably assessed by native T1 mapping without the administration of gadolinium contrast agent. In addition, cardiac magnetic resonance–derived ECV showed excellent agreement with histological extracellular space. [Display omitted]